2006
DOI: 10.1016/j.cell.2006.09.037
|View full text |Cite
|
Sign up to set email alerts
|

The Highly Conserved LepA Is a Ribosomal Elongation Factor that Back-Translocates the Ribosome

Abstract: The ribosomal elongation cycle describes a series of reactions prolonging the nascent polypeptide chain by one amino acid and driven by two universal elongation factors termed EF-Tu and EF-G in bacteria. Here we demonstrate that the extremely conserved LepA protein, present in all bacteria and mitochondria, is a third elongation factor required for accurate and efficient protein synthesis. LepA has the unique function of back-translocating posttranslocational ribosomes, and the results suggest that it recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
234
2
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(259 citation statements)
references
References 36 publications
18
234
2
5
Order By: Relevance
“…In the context of our model, this finding would suggest that LepA may recognize and bind to the functional state induced by the oxazolidinone i.e., an A/O state and via back-translocation of the tRNA attempt to rescue the stalled ribosome, consistent with the proposed role of this protein during elongation under stress conditions (Fig. S5b) (37). In this regard, we note however that a ⌬lepA strain has an identical IC 50 for oxazolidinones as the wild-type strain (12), suggesting that the binding of LepA is a consequence, rather than a cause, of the functional state induced by the oxazolidinones.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In the context of our model, this finding would suggest that LepA may recognize and bind to the functional state induced by the oxazolidinone i.e., an A/O state and via back-translocation of the tRNA attempt to rescue the stalled ribosome, consistent with the proposed role of this protein during elongation under stress conditions (Fig. S5b) (37). In this regard, we note however that a ⌬lepA strain has an identical IC 50 for oxazolidinones as the wild-type strain (12), suggesting that the binding of LepA is a consequence, rather than a cause, of the functional state induced by the oxazolidinones.…”
Section: Discussionsupporting
confidence: 63%
“…LepA is a translational GTPase that binds to POST state ribosomes inducing a back-translocation to the PRE state (37). We recently determined a cryo-electron microscopy reconstruction of LepA trapped in the process of back-translocating tRNAs by using the nonhydrolyzable GTP analogue GDPNP (50).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, overexpression of Guf1 exhibits a pronounced negative effect, 23 consistent with the observation that overproduction of LepA stalls translation in bacteria. 30 We found that overexpression of hGUF1 and hGUF1 A609S in Δguf1 had comparable effect on growth, mitochondrial protein expression and translation (Supplementary Figure S5A and D and Supplementary Materials). Likewise, hGUF1 and hGUF1 A609S were both able to suppress the strong synthetic growth defect of the oxa1ΔC Δguf1 double mutant on plates and in direct competition assays (Figure 3, Supplementary Figure S6A and B and Supplementary Materials).…”
Section: Resultsmentioning
confidence: 74%
“…The variant we identified in the WS family substitutes an alanine residue of the C-terminal Domain (CTD) that is conserved in all eukaryotes from budding yeast to human and the majority of prokaryotes (A609; an A residue is found at this position in 497 out of 539 EF4/GUF1 alignments; Supplementary Figure S4). The CTD, which is not found in other translational GTPases, 30 participates in the binding of the tRNA molecule via a beta-sheet 28 (Figure 2b and c). GUF1 is able to back-translocate the tRNA on ribosomes and as increasing amount of the protein resulted in reduced translational error rates, it was suggested that EF4 controls the fidelity of translation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation